Response of Broilers to Alternative Dietary Crude Protein Regimen - Oyedeji, J.O.; Olasupo, O.O.; Ekunwe, P.A.; Okugbo, O.T. (International Journal of Poultry Science, 2005)
An experiment was conducted to evaluate the use of a single diet containing 18% crude protein (CP) and 3000kcal/kgME as an alternative feeding regimen to 3 other conventional feeding standards for broiler production. Three hundred and twenty (320) Anak broilers were randomly divided into four treatment groups. The first three groups served as control while the 4th was the tested treatment. Broilers in group 1(G1) representing control 1 were fed diet with 23% CP 0-3 weeks, 20% CP 3-6 weeks and 16% CP 6-8 weeks. While those in group 2 (G2) representing control 2 were fed diet with 23% CP 0-6 weeks and 14% CP 6-8 weeks. Also broilers in group 3 (G3) representing control 3 were fed diet with 20% CP 0-4 weeks and 16% CP 4-8 weeks, while those in group 4 were fed 18% CP 0-8 weeks. All diets contained 3000kcal/kg of metabolizable energy. The birds were kept in battery brooder cage for 8 weeks. Feed and water were supplied ad libitum. At the 8th week, 10 birds were randomly selected from each of the four treatment groups and starved for 18 hours. They were killed by cervical dislocation and used to determine the carcass parameters. Performance results at 8 weeks showed that broilers fed on 18% CP and 3000kcal/kg ME had the lowest feed intake (P0.05) and better feed to gain ratio than the third control group (p0.05). Dietary crude protein CP 18% and 3000kcal/kgME for broilers resulted in better carcass weight, breast meat yield and gizzard weight when compared with the controls (P